Macroplastics pollution in the Surma river in Bangladesh: a threat to fish diversity and freshwater ecosystems - Abdullah, Abul Hasnat (2023)
Plastic pollution is one of the pressing issues in freshwater ecosystems that may further contribute to coastal pollution. The present study aimed to address the state of macroplastics pollution in the Surma River system, Bangladesh. Six sampling sites were allocated in the river starting from upstream to downstream, water parameters and fin fish assemblage were recorded, and plastic debris was collected from each site. Afterward, macroplastics were categorized and weighed to measure their abundance. Previous data on rainfall, water discharge, and depth were aggregated to study the trend of river depth changes. A survey was conducted to identify the possible sources of plastic pollution in the river and awareness of the pollution. The results showed that Kazir Bazar (Site 4) and Beter Bazar (Site 5), comparatively contained poor water quality, diverse macroplastics categories, and higher macroplastics abundance. The water pollution index (WPI) also ranked the above sites as extremely polluted. Similarly, biodiversity indices revealed lower diversity at Site 4 and Site 5. The river depth analysis revealed that there was no remarkable tendency to change the depth. To conclude, the Surma River system is being polluted due to inadvertent plastic dumping. Contemporary awareness is highly required, and proper policies should be implemented to minimize the detrimental effects of macroplastics.